Servicescape of Fitness Facilities and Customer Satisfaction: A Comparative Kano Analysis of Korean and Chinese Consumers - Long-Zhe Li; Sung-Kwang Kim; Jinho Yoo; Kyong-ken Choi (The Asian Journal of Kinesiology)
OBJECTIVES This study explores the impact of fitness facility servicescapes on customer satisfaction and compares the differences between Korean and Chinese consumers using the Kano model. The research aims to identify key service elements influencing satisfaction, analyze cultural and socioeconomic factors affecting consumer preferences, and provide strategic insights for market-specific service design. METHODS An online survey via Google Forms was conducted with 158 Korean participants (Seoul and Gyeonggi regions) and 216 Chinese participants (Liaoning Province). The Kano model and Timko coefficient were applied to classify service quality attributes (Attractive, One-dimensional, Must-be, Indifferent, Reverse) and quantify satisfaction (SI) and dissatisfaction (DSI) impacts. Six servicescape dimensions (equipment status, facility systems, spatial design, ambiance, accessibility, fitness tech) were analyzed using SPSS 26 for reliability testing (Cronbach’s α ≥ 0.70). RESULTS Korean consumers prioritized Attractive Quality (A) elements like equipment innovation and ambiance (e.g., smart lighting), while Chinese consumers emphasized Must-be Quality (M) for standardized infrastructure. Timko analysis revealed high SI for real-time monitoring systems in Korea and localized digital content in China. Differences in socio-cultural contexts significantly influenced preferences, with Korea favoring tech-integrated experiences and China prioritizing functional reliability. CONCLUSIONS The study highlights culture-specific strategies: Korea should focus on high-tech, emotionally resonant servicescapes, while China requires standardized infrastructure and localized digital content. Integrating the Kano-Timko framework enables dynamic quality management, optimizing resource allocation for global fitness industries.